HYPNOPARENTING EFFECTS TOWARDS FATIGUE AS AN IMPACT OF CHEMOTHERAPY AMONG PEDIATRIC PATIENTS WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Sapariah Anggraini (Fakultas Ilmu Keperawatan Universitas Indonesia, 2018)
The management of fatigue among pediatric patients with lymphoblastic leukemia does not become a priority apart from the cancer management itself. Hence, it is necessary to put an attention towards this issue by giving another complementary therapy for the patient called hypnoparenting. By implementing hypnoparenting will decrease the level of fatigue because of the chemotherapy process. Therefore the purpose of study was to investigate the effect of hypnoparenting towards fatigue prevalence as an impact of chemotherapy among pediatric patients with Acute Lymphoblastic Leukemia. This research utilized quasi experiment before after study. The population of the study was pediatric patients (5-12 years old) who suffered by Acute Lymphoblastic leukemia under chemotherapy treatment at RSUD Ulin Banjarmasin. The study was started on Mei 2016 until June 2016 with the total participants were 30 pediatrics patients. The data analysis used dependent t-test with 95% CI and p value <0.05. According to the mean score of 30 patients in the range of age 5-12 years revealed ; before and after hypnoparenting implementation, The mean score was different 5.30 and p value 0.0003, 95% CI (2.681 – 7.919). There was a significant difference on fatigue level among the patients before and after hypnoparenting implementation. Keyword: acute lymphoblastic leukemia, fatigue, hypnoparenting Abstrak Fenomena yang sering terjadi, manajemen kelelahan untuk pasien anak dengan kanker belum menjadi prioritas dalam manajemen efek samping terapi kanker. Tujuan dari penelitian ini untuk mengetahui pengaruh hypnoparenting terhadap kejadian kelelahan akibat kemoterapi pada anak dengan acute lymphoblastic leukemia di RSUD Ulin Banjarmasin. Penelitian ini menggunakan desain studi quasi eksperimen dengan jenis before after study. Populasi dalam penelitian ini adalah anak usia 5-12 tahun yang menderita kanker dengan jenis acute lymphoblastic leukemia yang sedang menjalani kemoterapi di RSUD Ulin Banjarmasin yang terdiri dari 30 orang anak dengan waktu penelitian dari Mei 2016 sampai Juni 2016. Analisa menggunakan uji beda 2 mean dependen dengan 95% CI dan p value < 0,05. Berdasarkan perhitungan rerata tingkat kelelahan pada anak usia 5 – 12 tahun yang berjumlah 30 responden didapatkan sebelum dan sesudah dilakukan hypnoparenting yakni beda mean sebesar 5,30 dan p value 0.0003, 95% CI (2.681 - 7.919). Terjadi penurunan rerata skor secara bermakna pada tingkat kelelahan sebelum dan sesudah dilakukan hypnoparenting. Kata Kunci: hypnoparenting, kelelahan, leukemia limfoblastik akut